Resolution of liver fibrosis requires myeloid cell–driven sinusoidal angiogenesis. Issue 6 (10th March 2015) - Kantari‐Mimoun, Chahrazade; Castells, Magali; Klose, Ralph; Meinecke, Anna‐Katharina; Lemberger, Ursula J.; Rautou, Pierre‐Emmanuel; Pinot‐Roussel, Hélène; Badoual, Cécile; Schrödter, Katrin; Österreicher, Christoph H.; Fandrey, Joachim; Stockmann, Christian
<x xml:space="preserve">Abstract</x> Angiogenesis is a key feature of liver fibrosis. Although sinusoidal remodeling is believed to contribute to fibrogenesis, the impact of sinusoidal angiogenesis on the resolution of liver fibrosis remains undefined. Myeloid cells, particularly macrophages, constantly infiltrate the fibrotic liver and can profoundly contribute to remodeling of liver sinusoids. We observe that the development of fibrosis is associated with decreased hepatic vascular endothelial growth factor (VEGF) expression as well as sinusoidal rarefication of the fibrotic scar. In contrast, the resolution of fibrosis is characterized by a rise in hepatic VEGF levels and revascularization of the fibrotic tissue. Genetic ablation of VEGF in myeloid cells or pharmacological inhibition of VEGF receptor 2 signaling prevents this angiogenic response and the resolution of liver fibrosis. We observe increased expression of matrix metalloproteases as well as decreased expression of tissue inhibitor of metalloproteases confined to sinusoidal endothelial cells in response to myeloid cell VEGF. Remarkably, reintroduction of myeloid cell–derived VEGF upon recovery restores collagenolytic acitivity and the resolution of fibrosis. Conclusion: We identify myeloid cell–derived VEGF as a critical regulator of extracellular matrix degradation by liver endothelial cells, thereby unmasking an unanticipated link between angiogenesis and the resolution of fibrosis. (Hepatology 2015;61:2042–2055)